Some Applications of Catas Operator to P-valent Starlike Functions - Abdusalam R. Ahmed (Surman Journal of Science and Technology, 2024)
The purpose of the present paper, is to investigate and study some new subclasses of p-valent starlike, convex, close-to-convex, and quasi-convex functions associated with Catas operator in the open unit disk . Inclusion relations are established, defined the integral operator of functions in these subclasses and some properties of them are discussed. Also defined combining operation between Catas operator with Libera integral operator for these subclasses in , also we use some Lammas and identities of operators to get and proof main results of these subclasses.